PENGALAMAN KELUARGA MENGHADAPI HOSPITALISASI PASIEN KRITIS DI RUANG ICU RS Dr. BRATANATA JAMBI - Mega Herawati; Fithriyani Fithriyani (Jurnal Akademika Baiturrahim Jambi, 2018)
Hospitalization is a process that for a reason of planning or emergency, which requires patients to stay in the hospital. Hospital patient care not only causes problems for the patient, but also for the family. The purpose of this study was to determine the family’s experience in dealing with hospitalization of critical patients in ICU Dr. Bratanata Hospital Jambi. This research is a qualitative research with phenomenology approach using Colaizzi model analysis which is implemented in Dr. Bratanata Hospital Jambi. Participants in this study were 5 participants with core family inclusion criteria who had been waiting for more than 7 days and were over 18 years old. Data collection techniques with in-depth interviews.The results of the study there is a Critical Hospitalization Patient Response in the ICU room for the family consisting of physical response include fatigue, body complaints and sleep disorders; Psychological responses include anxiety, tension, fear and sadness; Social responses include reduced communication and new experiences.